A Geografia da indústria de lanifícios na União Europeia - Pires, Iva (Finisterra, 1996)
THE GEOGRAPHY OF WOOL TEXTILES IN THE EU - In the wool textiles, unlike cotton, the competition comes mainly from other industrialised countries. The textile specificity, normally produced in small quantities, incorporating design and frequently adapted to fashion, prevents mass consumption. On the other hand the need of qualified and skilled workforce prevents the relocation to countries that can only offer low wages. Thus the EU maintains its world leading position as wool textile producer, the dominant role belonging to Italy, Germany and France. Another important feature is specialisation of these countries in a specific segment of the wool "filière". In the last years the flows of wool products among the EU countries has been growing and theystill trade mostly among them. Consequentely, the productive space has become more cohesive with a simultaneous reinforcement of the centre-periphery model.